Sistem Supply Chain Crude-Palm-Oil Indonesia dengan Mempertimbangkan Aspek Economical Revenue, Social Welfare dan Environment - Kuncoro Harto Widodo; Aang Abdullah; Kharies Pramudya Dwi Arbita (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2010)
Crude-Palm-Oil (CPO) is an agro-industrial commodity which has a strategic value to be developed for Indonesian economy and social welfare. Production and export of Indonesian CPO increase progressively in the view years so that CPO is one of the pre-eminent products of Indonesia. On the other hand, however, they could give two negative impacts. First, a less CPO supply for domestic market as a result of export growing. Second, a worse environment as an effect of the opening new palm plantations. We, therefore, construct and simulate the system model for analyzing the relationships between the components and for describing their behaviour within the supply chain of CPO by using a dynamic model. The result shows that in the next 30 years, the revenue of Indonesian CPO industries tends to increase. The biggest revenue will be achieved in the year 23rd. The maximum addition of plantation employees is in the year 7th as well as in the year 17th. Deforestation would be the highest in the year 7th and 17th in which 2008 as a basic year.